Predictors of smoking cessation among adult smokers in Malaysia and Thailand: Findings from the International Tobacco Control Southeast Asia survey - Lin Li (2018)
Introduction: Limited longitudinal studies on smoking cessation have been reported in Asia, and it remains unclear whether determinants of quitting are similar to those found in Western countries. This study examined prospective predictors of smoking cessation among adult smokers in Thailand and Malaysia. Methods: Four thousand and four smokers were surveyed in Malaysia and Thailand in 2005. Of these, 2,426 smokers were followed up in 2006 (61% retention). Baseline measures of sociodemographics, dependence, and interest in quitting were used to predict both making quit attempts and point prevalence maintenance of cessation. Results: More Thai than Malaysian smokers reported having made quit attempts between waves, but among those who tried, the rates of staying quit were not considerably different between Malaysians and Thais. Multivariate analyses showed that smoking fewer cigarettes per day, higher levels of self-efficacy, and more immediate quitting intentions were predictive of both making a quit attempt and staying quit in both countries. Previous shorter quit attempts and higher health concerns about smoking were only predictive of making an attempt, whereas prior abstinence for 6 months or more and older age were associated with maintenance. Discussion: In Malaysia and Thailand, predictors of quitting activity appear to be similar. However, as in the West, predictors of making quit attempts are not all the same as those who predict maintenance. The actual predictors differ in potentially important ways from those found in the West. We need to determine the relative contributions of cultural factors and the shorter history of efforts to encourage quitting in Asia. © The Author 2010. Published by Oxford University Press on behalf of the Society for Research on Nicotine and Tobacco. All rights reserved.